Effects of dried sugar beet root based concentrates level on body components and carcass characteristics in Nubian goat male kids - Elimam, Mohamed; Musa, Areeg; Siddig, Fawgia (Gezira Journal of Agricultural Science, 2018)
The increasing meat demand and prices and nutritional awareness in the Sudan showed that goat meat production is attractive. Nubian goat is the main dairy breed and culled males are important for meat production. However, nutrition is the main constraint for goat production. Sorghum cobs residues ( Seewa ) is cheap, abundant and is supplemented to improve the nutritive value. Sugar beet is introduced for sugar production in the Gezira State and is a valuable feed. There is no information on dried sugar beet roots (DSBR) based concentrates level on Nubian kids performance and carcass characteristics. Therefore, this study was conducted to furnish this vital information. Twelve Nubian male kids at 6 month old were housed in individual pens with feed and water troughs and allocated at random to three feeding levels. They were fed upgraded Seewa (UGS) ad lib . at 8 am and 4 pm and DSBR based concentrates at 0, 250g and 500g in two meals before UGS. The animals were fed for 8 weeks including a 10 days preliminary period and were then fasted overnight, weighed and slaughtered. Data was statistically analayzed using the completely randomized design. Slaughter weight, empty body weight (EBW), hot carcass weight and dressing percentages on live body weight (LBW) and EBW increased with concentrates level. Dressing percentages on LBW significantly (P≤0.05) increased and muscle, bone and fat percentages were not significantly affected with concentrates level. Bone and fat percentages increased with concentrates level and muscle percentage increased with concentrates level up to 250g and then decreased at 500g. Muscle:bone decreased and muscle:fat generally increased with concentrates level, but differences were not significant (P>0.05). Head, feet, skin, intestines, liver, omentum and testicles increased in weight and stomach, heart, lungs, mesentery and tail generally increased in weight with concentrates level. Spleen weight was similar in all concentrates levels. Blood, pancreas and kidneys and renal fat weight decreased with concentrates level. Most body components were  heaviest in animals fed 500g concentrates. All body components weights were not significantly (P>0.05) affected with concentrates level, except stomach, testicles and omentum. Concentrates level had no significant effect on body components percentages. It is recommended to use DSBR based concentrates and upgraded Seewa in fattening Nubian male kids.